2015
DOI: 10.1262/jrd.2014-112
|View full text |Cite
|
Sign up to set email alerts
|

Addition of D-penicillamine, hypotaurine, and epinephrine (PHE) mixture to IVF medium maintains motility and longevity of bovine sperm and enhances stable production of blastocysts <i>in vitro</i>

Abstract: The present study aimed to establish an efficient system for bovine embryo production by in vitro fertilization (IVF) that can achieve stable normal fertilization and blastocyst developmental rates in any bull without optimization of the sperm concentration in IVF medium. We examined the effects of a PHE mixture (20 μM D-penicillamine, 10 μM hypotaurine and 1 μM epinephrine), theophylline (2.5 mM), and sperm concentration (1, 2 or 5 × 106 cells/ml) on fertilization and blastocyst developmental rates. High clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…In spite of the well‐known effects of the PHE in improving the oocyte penetration, the pronuclear formation and the efficiency of in vitro embryo production in cattle (Gonçalves et al ., ; Kang et al ., ), there are not evident effects on sperm quality after exposure to this mixture. PHE exposure does not affect the MMP as well as the integrity of sperm membranes and DNA (Gonçalves et al ., ).…”
Section: Discussionmentioning
confidence: 77%
“…In spite of the well‐known effects of the PHE in improving the oocyte penetration, the pronuclear formation and the efficiency of in vitro embryo production in cattle (Gonçalves et al ., ; Kang et al ., ), there are not evident effects on sperm quality after exposure to this mixture. PHE exposure does not affect the MMP as well as the integrity of sperm membranes and DNA (Gonçalves et al ., ).…”
Section: Discussionmentioning
confidence: 77%
“…As agglutination occurs when trying to capacitate ram spermatozoa in TALP, it was important to assess if the inclusion of PEN in this medium would interfere in the capacitation process. It would seem unlikely as low doses of PEN (20 mM), in conjunction with hypotaurine and epinephrine (PHE), have been included in multiple bovine IVF protocols to improve oocyte penetration and embryo quality (Miller et al 1994, Goncalves et al 2014, Kang et al 2015. PEN has also been used in protein-free media to promote capacitation (Andrews & Bavister 1989, Keskintepe & Brackett 1996.…”
Section: Discussionmentioning
confidence: 99%
“…In frozen/thawed bovine spermatozoa, the mixture of penicillamine, hypotaurine and epinephrine (PHE mixture) improves mitochondrial membrane potential and promotes better maintenance of intracellular pH upon incubation at room temperature for 4 hr (Boni, Gallo, & Cecchini, 2017). Similarly, the combination of the PHE mixture and theophylline improves sperm motility and sperm penetration of bovine oocytes (Kang et al, 2015). Another study reported that although the IVF media supplementation with a heparin and PHE mixture affects bovine sperm quality, it contributes to sperm capacitation, due to an improvement of pronuclear formation and early embryonic development during bovine IVF procedures (Goncalves, Barretto, Arruda, Perri, & Mingoti, 2014).…”
Section: Discussionmentioning
confidence: 99%